ChemInform Abstract: The Stannides Nd3Pd5Sn5, Gd3Pd4.96(1)Sn5, and GdPdSn. Issue 19 (May 2015) - Heying, Birgit; Rodewald, Ute Ch.; Poettgen, Rainer
Abstract: Nd3 Pd5 Sn5 and Gd3 Pd4.96 Sn5 are obtained by arc‐melting of the elements.